Anti-oxidation and anti-aging activity of polysaccharide from Malus micromalus Makino fruit wine - Hui, Yang; Jun-li, Hua; Chuang, Wang (International journal of biological macromolecules, 2019)
Malus micromalus Makino fruit wine was used as a raw material and a water soluble polysaccharide (MWP-2) was successfully separated from it by fractionated extraction, alcohol precipitation, macroporous resin purification, cellulose column purification, running water dialysis, and vacuum freeze drying. The structure of MWP-2 was preliminarily analyzed by high performance gel-permeation chromatography (HPGPC), ion chromatograph (IC) and FT-IR. The anti-oxidation and the anti-aging activity of MWP were studied. Results showed that the relative molecular mass of MWP-2 was 1 × 105 Da and it was composed of galactose, glucose, mannose and fructose in the mole ratio of 1:33.2:8.4:7.2. Antioxidant experiments in vitro showed that MWP had different degrees of scavenging effects on the hydroxyl radicals, DPPH (1,1-two phenyl-2-bitter hydrazine radical) free radical, and superoxide radicals, presenting a certain dose effect relationship. However, the anti-aging experiments in vivo showed that MWP could significantly inhibit the apoptosis of cerebral cortex cells and the formation of lipid peroxide in the cerebral cortex of aging model mice, improve the activity of the antioxidant enzyme system, and exert a certain anti-aging effect. •A water soluble polysaccharide (MWP-2) was separated from a fruit wine.•MWP-2 was composed of galactose, glucose, mannose and fructose.•MWP had scavenging effects on the hydroxyl radicals, DPPH free radical, and superoxide radicals.•MWP could inhibit the apoptosis of cerebral cortex cells and the formation of lipid peroxide in the aging model mice.